Inter‐annual variations of precipitation over the monsoon transitional zone in China during August–September: Role of sea surface temperature anomalies over the tropical Pacific and North Atlantic. (26th November 2018) - Zhao, Wei; Chen, Wen; Chen, Shangfeng; Yao, Shuai‐Lei; Nath, Debashis
Abstract : The present study investigates inter‐annual variations of precipitation during transitional periods (August–September) of the rainy season over the monsoon transitional zone (MTZ) in China. More precipitation tends to occur over the MTZ during August–September when a significant anticyclonic anomaly simultaneously appears over the western North Pacific (WNP). Prominent southerly wind anomalies induced by the anticyclonic anomaly over the WNP contribute to more precipitation over the MTZ via transporting abundant water vapor northward. Sea surface temperature (SST) cooling in the tropical central‐eastern Pacific and SST warming in the northern tropical Atlantic (NTA) are crucial to the formation of the anticyclonic anomaly over the WNP. In addition, it is showed that the significant impact of the SST warming in the NTA on the WNP anticyclonic anomaly is independent of the SST cooling in the tropical central‐eastern Pacific. Atmospheric general circulation model experiments demonstrate that the SST warming over the NTA can produce an anticyclonic anomaly over the WNP via modulation of the Walker circulation with upward motion anomalies over the NTA and downward motion anomalies over the tropical central Pacific. The resultant negative precipitation anomalies over the tropical central Pacific further trigger an anticyclonic anomaly over the WNP via a Gill‐type atmospheric response. The results suggest that SST anomalies in the tropical central‐eastern Pacific and the NTA play a key driver for inter‐annual variations of precipitation over the MTZ in China during August–September. Abstract : More precipitation tends to occur over the MTZ during August–September when a significant anticyclonic anomaly simultaneously appears over the western North Pacific (WNP). Prominent southerly wind anomalies induced by the anticyclonic anomaly over the WNP contribute to more precipitation over the MTZ via transporting abundant water vapour northward. Sea surface temperature (SST) cooling in the tropical central‐eastern Pacific and SST warming in the northern tropical Atlantic (NTA) are crucial to the formation of the anticyclonic anomaly over the WNP. In the figure, (a) SST (unit: °C), and (b) 500 hPa omega (unit: 10 −3 Pa/s) anomalies during August–September obtained by regression upon the simultaneous August–September MTZI. Values of 500 hPa omega over the land in (b) are omitted. Stippling regions in (a, b) indicate SST and omega anomalies significant at the 95% confidence level, respectively. Positive (negative) value of omega indicates downward (upward) motion anomalies. (c) Correlation coefficients of the August–September MTZI with the 2‐monthly mean Niño3.4 index (blue solid line), NTA SST index (red solid line), and NTA_res SST index (red dashed line) from preceding February–March to following October–November. Definitions of the Niño3.4 index, NTA SST index, and NTA_res SST index are provided in the main text. Horizontal dashed lines in (c) indicate correlation coefficients significant at the 95% confidence level.